Features of the Drug Therapy of Children with Systemic Juvenile Idiopathic Arthritis: Analysis Results of the All-Russian Register of the Union of Pediatricians of Russia - E. I. Alexeeva; O. L. Lomakina; S. I. Valieva; T. M. Bzarova; I. P. Nikishina; Ye. S. Zholobova; G. G. Torosyan; S. R. Rodionovskaya; M. I. Kaleda; L. A. Galstyan; I. B. Alakaeva; Ye. A. Korotkova; et al. ("Paediatrician" Publishers LLC, 2016)
Objective: Our aim was to study features of the drug therapy of children with systemic juvenile idiopathic arthritis (sJIA).Methods: We conducted a retrospective data analysis included in the Register of sJIA cases, for the period from 2002 to 2015.Results: The indicators of 384 children with sJIA are studied. Prior to the diagnosis verification, all patients were prescribed to intake antipyretic agents, 98% - antibiotics. After the diagnosis, non-steroidal anti-inflammatory drugs (NSAIDs) were intaken by 282 (73.4%) patients: diclofenac sodium - by 163 (40.1%), nimesulide - by 88 (22.9%) patients. The average duration of NSAID intake from 2002 to 2015 decreased from 81.5 ± 115.3 to 3.3 ± 3.7 months (p < 0.001). Prior to the diagnosis verification, glucocorticoids were received intravenously or intramuscularly by 265 (69.0%) patients, orally - 176 (45.8%). Totally, glucocorticoids were received by 330 (85.9%) patients: methylprednisolone - 300 of 384 (78.1%), prednisolone - 174 (45.3%), there were totally 1855 prescriptions in 668 patients. The average duration of glucocorticoid intake from 2002 to 2015 decreased from 13.7 ± 26.7 to 5.0 ± 3,8 months (p < 0.001). As a disease-modifying drug, methotrexate was intaken by 237 (61.7%), Cyclosporin - by 193 (50.6%) patients. There were totally 809 prescriptions of genetically engineered biological preparations (GIBP) in 430 patients: in 2002-2005-8, in 2011-2015-602 in 397 patients (p = 0.001). Tocilizumab is intaken by 210 (52.9%) of 397 patients, kanakinumab - 37 (9.3%) patients. The disease duration from the manifestation to the prescription of immunosuppressive drugs from 2002 to 2015 decreased from 27.3 ± 23.9 to 1.0 ± 0 months (p < 0.001), GIBP prescriptions - from 70.7 ± 26.3 to 0.5 ± 0.7 months, respectively (p < 0.001).Conclusion: In 13 years there have been positive changes in the antirheumatic therapy in children with sJIA - the duration of NSAIDs and glucocorticoids intake reduced, the period between diagnosis verification and immunosuppressants and GIBP prescription decreased. However, it is still widely used antibiotics, non-selective NSAIDs and glucocorticoids.